(untitled) (Academia Journal of Medicine, 2025)
Chronic Kidney Disease (CKD) is a progressively debilitating condition, primarily affecting individuals with diabetes mellitus and hypertension, contributing significantly to global morbidity and mortality rates. As of 2021, CKD has emerged as the 9th leading cause of death worldwide. In patients with CKD, renal function declines gradually over time, often resulting in severe complications. Conventional treatments like dialysis and renal replacement therapy remain financially inaccessible to many, leading to a growing interest in alternative medical systems such as Ayurveda. Ayurveda provides a unique perspective on CKD, categorizing it under Madhyama rogamarga vyadhi, associated with accumulated kleda (excessive bodily fluids) throughout the body. Though the kidney is not explicitly mentioned in classical Ayurvedic texts, it can be correlated with vrikka. The embryological origin of vrikka is linked to medas (adipose tissue) and rakta (blood), which, when disturbed by improper diet and lifestyle, contribute to the pathogenesis of CKD. Ayurvedic management focuses on restoring balance in these dhatus, offering a holistic treatment approach that may complement conventional therapies. A case report of a 57-year-old male diagnosed with CKD stage V in 2010 illustrates the effectiveness of Ayurvedic interventions. The patient, presenting with recurrent vomiting, loss of appetite, decreased urine output, disturbed sleep, constipation, and right lower limb cellulitis, underwent Panchakarma therapy at Jeena Sikho Lifecare Limited Hospital, Derabassi, Chandigarh, in April 2024. He followed an Ayurvedic diet, practiced yoga and made lifestyle modifications, along with Ayurvedic medication, leading to positive clinical outcomes. This case underscores the potential of an integrative Ayurvedic approach to managing CKD effectively.